Answer: x = 60/11
Explanation:
-1 + 4 (6x + 3) = 1/2 (-10x - 10) -5
Multiply the 1/2 with -10x, and -10.
Let's look on the side that we are working on now.
New equation:
- 1 + 4 (6x + 3) = -5x - 5 - 5
-5-5= -10
-1+4(6x+3)=-10-5x
Next we remove the brackets.
-1 + 4 * 6x + 3 = -10x -5
Now we bring the x's on one side and the non-x's on the other. When we bring a positive x on the other side of an equal sign, it becomes negative. If we bring a negative x on the other side of an equal sign, it becomes positive.
10x * 6x = 1 - 4 - 3 - 5
60x = 1 - 12
60x = -11
x = 60/11
* I had to do this all on paper *